Financial Ratio Analysis to Measure Company Performance PT. Garudafood Putra Putri Jaya Tbk. - Dearmando Novhero Damanik; Haga Creis Tentry; Ika Fitriani Sukur; Ranti Octavia Panjaitan; Sabda Dian Nurani Siahaan (Asian Journal of Applied Business and Management, 2023)
The purpose of this research is to analyze the financial performance of PT. Garudafood Putra Putri Jaya in 2020, 2021, and 2022 using liquidity, solvency, activity, and profitability ratios. The data used in this study are the annual financial statements of PT. Garudafood Putra Putri Jaya during the period. The type of research used is comparative descriptive. The overall results of the study show that PT. Garudafood Putra Putri Jaya is healthy, and the company can be used in the long term because PT. Garudafood Putra Putri Jaya has sufficient capabilities to fulfill its financial obligations.